Effect of Piperine, Quercetin, Polysorbate 80 on the Oral Bioavailability of Losartan in Male Wistar Rats - Rewanthwar, Swathilatha; Lakshmi, P.K. (Pharmaceutical Nanotechnology, 2014)
Scope: P-glycoprotein (P-gp) is found to play a very significant role in intestinal transport of losartan, an antihypertensive drug with variable and low oral bioavailability (33%), is a substrate for both CYP 3A4 and P-gp. This makes P-gp inhibition a logical strategy for improving losartan’s oral efficacy and reducing its toxicity. Thus, we investigated whether the co-administration of piperine, quercetin, and polysorbate 80 could increase losartan’s pharmacokinetic activity in vivo. Methods and results: We determined the effect of piperine, quercetin, and polysorbate 80 coadministered with losartan on plasma levels in rats by HPLC assay. Rats were administered losartan (10mg/kg; oral gavage) or losartan (10mg/kg; oral gavage) +piperine (10mg/kg; oral gavage) or losartan (10mg/kg; oral gavage) +quercetin (7.5mg/kg; oral gavage) or losartan (10mg/kg; oral gavage) +polysorbate 80 (1%w/v of drug solution; oral gavage), and the plasma levels of losartan were analyzed at different time intervals. Inhibition of p-gp activity resulted in an increased area under the curve (AUC), maximum plasma concentration (Cmax), and mean residence time (MRT) of losartan when compared to losartan alone. Conclusions: Losartan is one of the most widely used antihypertensive agents. Dietary constituents and pharmaceutical excipients are important agents modifying drug transport. In our studies, consumption of piperine, quercetin, and polysorbate 80 increases the therapeutic efficacy of losartan without inducing adverse effects on the treated mice.
Keywords: losartan